2014
DOI: 10.5511/plantbiotechnology.14.0827a
|View full text |Cite
|
Sign up to set email alerts
|

Plant–plant communication mediated by airborne signals: ecological and plant physiological perspectives

Abstract: When exposed to herbivore-infested plant volatiles or volatiles from artificially damaged plants, intact plants enhance their defense against herbivores. This phenomenon is called plant-plant communication. Here, we outline studies on plant-plant communication from both ecological and plant physiological perspectives. Regarding the ecological perspective, we give an overview of studies showing that plant-plant communication affect direct and indirect defense levels of exposed plants, and herbivore performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 55 publications
0
40
1
Order By: Relevance
“…Plant volatiles may provide information regarding plant condition and can influence the behaviour of organisms other than herbivores (Sugimoto, Matsui, & Takabayash, ). Studies demonstrated that plants have the ability to respond to volatile infochemicals emitted from neighbouring plants and thus, plants also serve as infochemical receivers (Yoneya & Takabayashi, ). Volatiles taken up by plants undergo glycosylation and glutathionylation, resulting in nonvolatile compounds that might have ecological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Plant volatiles may provide information regarding plant condition and can influence the behaviour of organisms other than herbivores (Sugimoto, Matsui, & Takabayash, ). Studies demonstrated that plants have the ability to respond to volatile infochemicals emitted from neighbouring plants and thus, plants also serve as infochemical receivers (Yoneya & Takabayashi, ). Volatiles taken up by plants undergo glycosylation and glutathionylation, resulting in nonvolatile compounds that might have ecological functions.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few volatiles and their corresponding UGTs have been functionally characterized due to the presence of hundreds of UGT‐encoding genes in most plant species (Yonekura‐Sakakibara & Hanada ; Caputi et al ; Song et al ) and substrate promiscuity of UGT enzymes (Jones & Vogt, ). In contrast to the intensively studied UGTs involved in the glucosylation of monoterpenols (Bönisch et al , ,b; Yoneya & Takabayashi, ; Ohgami et al , ) and nonvolatile diterpenoids (C20) (Richman et al , ; Nagatoshi et al , ; Sun et al , ), the UGTs involved in the glucosylation of sesquiterpenes have been scarcely documented, possibly due to the relative rarity of sesquiterpene glycosides in the plant kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…As examples of notable capabilities of the plants that can be considered like some kind of reasoning can be mentioned (Goh, Nam, & Park, ; Volkov, Carrell, Baldwin, & Markin, ): discriminating negative and positive experiences and learning from past experiences, communication capability, accurate computing their circumstances. Yoneya and Takabayashi () analyze the complex communication between plants from the same or different species. By communicating, plants can form a highly complex system as a whole.…”
Section: Extroptfact Algorithm For Establishment Of Optimal Number Ofmentioning
confidence: 99%